High-Power ZBLAN Glass Fiber Lasers: Review and Prospect. (29th March 2010) - Zhu, Xiushan; Peyghambarian, N.
Abstract : ZBLAN (ZrF4 -BaF2 -LaF3 -AlF3 -NaF), considered as the most stable heavy metal fluoride glass and the excellent host for rare-earth ions, has been extensively used for efficient and compact ultraviolet, visible, and infrared fiber lasers due to its low intrinsic loss, wide transparency window, and small phonon energy. In this paper, the historical progress and the properties of fluoride glasses and the fabrication of ZBLAN fibers are briefly described. Advances of infrared, upconversion, and supercontinuum ZBLAN fiber lasers are addressed in detail. Finally, constraints on the power scaling of ZBLAN fiber lasers are analyzed and discussed. ZBLAN fiber lasers are showing promise of generating high-power emissions covering from ultraviolet to mid-infrared considering the recent advances in newly designed optical fibers, beam-shaped high-power pump diodes, beam combining techniques, and heat-dissipating technology.